English - Indonesian Translation of Idiomatic Expressions Found in The Adventure of Tom Sawyer: Strategies Used and Resulted Equivalence - Ahdillah, Muhammad Zidni Ilman; Hartono, Rudi; Yuliasri, Issy (Universitas Negeri Semarang, 2020)
This study was focused on the analysis of idiomatic expressions translated from English into Bahasa Indonesia from novel Ã¢â‚¬Å“The Adventure of Tom Sawyer. The analysis included on the translation strategies utilized by translator in transferring idiomatic expression and the relationship toward translation strategies and equivalence of idiomatic expression translation. The results of the study showed that (1) free translation strategy became the frequent strategy used by the translator of the novel which led to the conclusion that in rendering idiomatic expression in the children literary book was mostly done by re-creating the idiomatic expressions in the target language. (2) the translator tended to re-create the words and phrases in the target language neglecting the words and grammatical units of source language in order to get the similar meaning and essence of the source language (3) the use of translation strategies in the translation of idiomatic expression had close relationship with the resulted equivalence of idiomatic expression in Indonesian. In translating the idiomatic expression, it is better if the translator knows the context of the situation where the narrator tells about the story in the novel to improve the quality of the translation. In addition, it is also recommended that the use of translation strategy in rendering idiomatic expression should be based on the genre of the text and also the target readers in order to achieve best quality of equivalence.